Comparative omics analyses in the identification of the genetic basis of differential aggressiveness in Sporisorium scitamineum, the causal agent of sugarcane smut disease - Ferreira, Pedro Fernando Vilanova (2025)
Sugarcane smut is a worldwide-spread plant disease caused by the biotrophic fungus Sporisorium scitamineum. The disease causes substantial yield losses in sugarcane crops and thus is a major threat to global production. Previous studies demonstrated that isolates from different genetic backgrounds have distinct variation in aggressiveness levels when infecting susceptible plants, but the genetic basis of aggressiveness is scarce and remains to be established. To understand genetic variability and transcriptional plasticity among isolates with these distinct phenotypes, chromosome-scale genome sequencing and transcriptional profiling were performed. Results demonstrated that the selected isolates have high genetic similarity, although they harbor nine highly polymorphic genomic islands with non-synonymous mutations. These mutations caused amino acid alterations in candidate secreted effector proteins and components of vesicular trafficking pathways. In addition, novel structural variants were found in mating-type loci associated with transposable elements relics. Transcriptomic profiling showed transcriptional reprogramming according to host resistance level, where the more aggressive isolate prioritized detox mechanisms, cell-wall degradation, and nitrogen starvation responses in the resistant genotype, while shifting to hyphal growth and proliferation in susceptible plants. Subcellular localization of selected candidate effectors demonstrated that these molecules target diverse cellular compartments in host cells. These findings reveal previously unknown genomic differences among isolates and show that the transcriptional regulation of S. scitamineum depends on the host. Together, these results provide new insights into the genetic basis of fungal aggressiveness and suggest that this characteristic in the species is likely a complex, quantitative trait. Future studies must prioritize complete sequencing of a wide and diverse pool of populations to account for phenotypic differences and to unravel mutations and genes leading to increased aggressive phenotypes.